International banking and cross-border effects of regulation: Lessons from the United States - José M. Berróspide; Ricardo Correa; Linda S. Goldberg; Friederike Niepmann (Federal Reserve Bank of New York, 2016)
Domestic prudential regulation can have unintended effects across borders and may be less effective in an environment where banks operate globally. Using U.S. micro-banking data for the first quarter of 2000 through the third quarter of 2013, this study shows that some regulatory changes indeed spill over. First, a foreign country's tightening of limits on loan-to-value ratios and local currency reserve requirements increase lending growth in the United States through the U.S. branches and subsidiaries of foreign banks. Second, a foreign tightening of capital requirements shifts lending by U.S. global banks away from the country where the tightening occurs to the United States and to other countries. Third, tighter U.S. capital regulation reduces lending by large U.S. global banks to foreign residents.
Keywords: F42; F44; G15; G21; 330; macroprudential policies; international banking; bank credit; spillovers